Sisal Territory-Bahia (Brasil): from the widespread precariousness to the strengthening of social activism - Lima, Jamille da Silva; Coelho, Agripino Souza (Geografares, 2017)
To analyze the coexistence between remaining structural conditions in the Território do Sisal and the emergence and strengthening of social activism is the centrapurpose of this article. To read this spatial context, we used the terms "permanence" and "emergencies", employed as a dialetic pair. The permanencies are manifested by the set of structural conditions and the historical particularity that was set up in the Território do Sisal (Bahia), recognized by the prevalence of the so-called physical and natural adver - sities related to drought, by a set of unfavorable social economic indicators exemplified by illiteracy, unemployment and among others, as well as the schemes of dominion and political clientelism. Emergencies are manifested in the mobilization and complexity of networks of social organizations, considered as social activism modality. This article is a result of a documental research and interviews with the most active social organization from Território do Sisal, during the years of 2010 and 2014. As a result, it was found that the social activisms of the Sisal Territory were searching for a political and moral direction conceived by social relations based on solidary cooperation, as well as on a more horizon - tal political and productive organization, and has been fighting for democratization of planning and public administration. Keywords : social activism, permanencies, emergencies, Sisal Territory.